Preliminary study of the presence of antibodies against excretory-secretory antigens from protoscoleces of Echinococcus granulosus in dogs with intestinal echinococcosis - David Carmena; Aitziber Benito; Jorge Martínez; Jorge A Guisantes (Memorias do Instituto Oswaldo Cruz, 2005)
The aim of the present study was to analyze the antibody response against excretory-secretory antigens (ES-Ag) from Echinococcus granulosus protoscoleces, using sera from dogs infected with E. granulosus and other helminths. ES-Ag were obtained from the first 50 h maintenance of protoscoleces in vitro. Immunochemical characterization was performed by immunoblotting with sera from dogs naturally infected with E. granulosus (n = 12), sera from dogs infected with helminths other than E. granulosus (n = 30), and helminth-free dog sera (n = 20). These findings were compared to those obtained from a somatic extract of protoscoleces (S-Ag). ES-Ag only showed four cross-reacting proteins of 65, 61, 54, and 45-46 kDa. Antigens with apparent masses of 89 and 50 kDa in ES-Ag and of 130 and 67 kDa in S-Ag were identified by sera of dogs infected with E. granulosus only, whereas a protein of 41-43 kDa was recognised by the majority of the sera from dogs with non-echinococcal infection. Employing ELISA to study the same sera, S-Ag revealed higher immunoreactivity than ES-Ag, but also showed higher cross-reactivity levels when sera from dogs with non-echinococcal infection were assayed in immunoblotting.